Free Nutritious Meals (MBG) Program Impact on Child Well-Being and Gender Equity in Indonesia - Ahmad Shofiyuddin Ichsan; Samsudin Samsudin; Nindya Rachman Pranajati; Mujawazah Mujawazah; Hendra Listya Kurniawan; Ahmad Auzai (Journal of Contemporary Gender and Child Studies, 2026)
Chronic malnutrition and stunting among Indonesian schoolchildren significantly impair cognitive development, attendance, and academic performance. The Free Nutritious Meals (Makan Bergizi Gratis/MBG) Program, launched in January 2025 under Indonesia's National Medium-Term Development Plan, addresses these challenges to support Sustainable Development Goal 4. This study examines implementation challenges and opportunities of the MBG program in improving basic education quality, emphasizing child well-being and gender equity. A qualitative systematic literature review analyzed policy documents and academic literature on school feeding interventions. Critical challenges include regulatory gaps, logistical inefficiencies, food safety concerns, suboptimal nutritional standards, administrative burdens, budget misallocation, weak inter-sectoral coordination, infrastructure deficits, limited capacity, and community resistance. However, significant opportunities exist: enhanced nutritional status, improved attendance and achievement, empowerment of local enterprises, and nutrition curriculum integration. The program holds substantial potential if addressed through comprehensive regulation, GPS-enabled management systems, rigorous monitoring, community engagement, and curriculum integration. Future research should employ longitudinal mixed-methods designs with international comparative frameworks to evaluate long-term effectiveness on child welfare and gender equity outcomes.